The Relationship Between Discipline Indicators and The Performance of Specialist Doctors in Outpatient Services of Hospital Dr.H Kumpulan Pane, Tebing Tinggi City in 2024 - Nasution, Sumiati; Sri Melda Br. Bangun; Okto Hebron (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Human resources, also known as